Analisis Perbandingan Kinerja Keuangan Bank Umum Syariah (Studi Kasus pada PT. Bank Muamalat dan PT. Bank Syariah Mandiri periode 2010-2014) - Muhammad Farid; Erna Listyaningsih (Universitas Malahayati, 2016)
Abstract. The objectives of this study is to compare the financial performance of sharia banks namely Bank Muamalat dan Bank Syariah Mandiri in the period of 2010-2014 by using the banking financial ratios. Financial ratios used in this study consisted of the CAR, NPF, BOPO, FDR, ROA, ROE, and NPM. This study uses data from financial statements of both banks during the last five years. Analysis used in this study is to compare the financial performance of sharia banks by using the independent sample t-test methods. This study finds that the average of sharia banks financial ratios of both banks is in the good conditions during the research period The results show that there is a significant difference of FDR rasio, however for CAR, NPF, BOPO, ROA, ROE, and NPM is insignificant difference.